The Effect of a Period of Aerobic Training on Serum Levels of IGF-1 and Thyroid Hormones in Women with Subclinical Hypothyroidism - Valipour Dehnou V (Complementary Medicine Journal of Faculty of Nursing and Midwifery, 2019)
Introduction: The IGF-1 affects physiological processes in the body and its serum levels decrease in patients with subclinical hypothyroidism. Therefore, the aim of this study was to investigate the effect of a period of aerobic training on serum levels of IGF-1 in women with subclinical hypothyroidism. Methods: In this quasi-experimental study, after obtaining written consents, 25 women with subclinical hypothyroidism (aged 35.59 ± 3.83 years old) were assigned to three groups: drug-aerobic training (N=8), aerobic training (N=7), and drug (N=10). Aerobic training included three 60-minutes sessions per week for 5 months. The drug group included the inactive participants who took only LT4 tablets. Serum levels of IGF-1, triiodothyronine (T3), thyroxine (T4) and thyroid-stimulating hormone (TSH) were measured in the three groups after 5 months. The data were analyzed using SPSS 16 through analysis of variance. Results: Aerobic activity resulted in significant changes in serum levels of IGF-1 and T4 (P≤0.05), This means that serum levels of IGF-1 in the drug- aerobic training and aerobic training groups were significantly higher than those in the drug group. Also, concentration of serum T4 was significantly lower in the drug- aerobic training and aerobic training groups than that in the drug group. No significant difference was observed in the concentrations of T3 and TSH among the groups. Conclusion: The results showed that 5 month of aerobic training increased the serum levels of IGF-1 in women with subclinical hypothyroidism, who are subjected to decreased IGF-1.